2019
DOI: 10.1038/s41439-019-0049-7
|View full text |Cite
|
Sign up to set email alerts
|

The CFTR gene variants in Japanese children with idiopathic pancreatitis

Abstract: The cystic fibrosis transmembrane conductance regulator ( CFTR ) gene has been reported as one of the pancreatitis susceptibility genes. Although many variants of CFTR have been reported in Caucasian patients, there are few data in Japanese patients. We aimed to survey CFTR variants in Japanese children with idiopathic pancreatitis. Twenty-eight Japanese paediatric patients with idiopathic pancreatitis were enroled, who were not previously di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The comprehensive systematic search and selection process identified 22 case-control studies that reported on some or all of the 9 CFTR BD variants and met the inclusion criteria for quantitative synthesis (Fig 1) [9,11,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. We noted significant geographic/ethnic differences in the distribution of the CFTR BD variants.…”
Section: Resultsmentioning
confidence: 99%
“…The comprehensive systematic search and selection process identified 22 case-control studies that reported on some or all of the 9 CFTR BD variants and met the inclusion criteria for quantitative synthesis (Fig 1) [9,11,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. We noted significant geographic/ethnic differences in the distribution of the CFTR BD variants.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, CFTR polymorphisms were believed to contribute to the genetic etiology of acute pancreatitis in young HTG Japanese patients (Fujita et al, 2022). The CFTR p.I566V was established most frequently in idiopathic and acute pancreatitis patients in the Chinese and Japanese populations (Chang et al, 2007;Iso et al, 2019). In the first study of the relationship between CFTR variants and hyperlipidemic pancreatitis, p.I566V was the most common variant present in patients with HTG with the onset of hyperlipidemic pancreatitis (HLP) compared with patients with HTG who do not have HLP (Chang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Participants comprised 90 Japanese patients (50 girls, 40 boys) with ARP or CP, all of whom were under 15 years old; median age at onset, 8.0 years (range, 2–15 years). A total of 63 of the 90 patients had already been identified as having variants in at least 1 of PRSS1 , SPINK1 , CFTR , CTRC , or CPA1 (19,20), so 27 newly unreported cases were included in this study (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%